TOPONIMI DESA DI KECAMATAN PASIR PUTIH KABUPATEN MUNA: TINJAUAN ANTROPOLINGUISTIK - Halfian Halfian; Salmin Salmin; Ashmarita Ashmarita (Seshiski: Southeast Journal of Language and Literary Studies, 2026)
This research is motivated by the lack of knowledge of the people in Pasir Putih District, regarding the origin or background, cultural meaning, and history of the formation of the names of the villages they have occupied. This research is important to do not only to describe the origin and meaning of village names, but also to document the local wisdom of the Muna community that has not been widely explored. The data collection method for this research uses interview techniques, recording techniques, and note-taking techniques. The results of this study indicate that the naming of villages in Pasir Putih District, Muna Regency predominantly uses the Muna language. The names of villages in Pasir Putih District, Muna Regency are based on three naming aspects, first, the aspect of embodiment which includes the geographical background (Kamosope Village and Liwumetingki Village), and which includes the natural environment background (Kogholifano Village and Pola Village). Second, the societal aspect in the form of community customs (Pola Village). Third, the cultural aspect in the form of folklore (myths and folklore) (Bumbu Village and Labulawa Village).